Development of TextBook to Support Merdeka Curriculum on the Atomic Structure of Phase E - Susanti, Aprilia; Mawardi, Mawardi; Suryani, Okta (research, training and philanthropy institution Natural Aceh, 2024)
As a result of the COVID-19 pandemic, it caused a very significant change in education. The learning was done online. So that makes the Indonesian student lose. The free curriculum also demands free study, as summarized in PROPELA. That's why research needs to be done to develop textbooks to support the study of the free curriculum matter, atomic structure phase E, and test the validity and practicality of this teaching material. This type of research is called Educational Design Research (EDR) with the Plomp model, which is: (1) preliminary research; (2) development or prototyping; and (3) assessment (not done). Research data from validation is insulated using Aiken's v formula, while registered data is analyzed in a present-day way. Based on the study's results, the teaching material has been valid, with an average score of 0.91. The use of the scripture is easy to understand and view, practical learning, and benefits of teaching, with an average score of 72%. This coursebook is valid and helpful through the formative tests that have been carried out. The final average value of 0.94 is proof of this validity. In addition, this coursebook is also equipped with mental model problems that are proven to help students solve existing problems. This is known from the responses of active and excellent students in solving these problems. In addition, the time spent working on the questions is also sufficient, so it only uses time outside of learning hours.